Competition in the training of the athletes of Special Olympics - Perederiy A.V (Kharkov National Pedagogical University, 2013)
The aim of the study is to characterize the competition as part of the system of training athletes of Special Olympics. It was determined that the specificity of the system of training athletes of Special Olympics is to focus on the demonstration of athletic performance. Determined that the results should contribute to the achievement of social adaptation and rehabilitation of athletes. Lack of dominance purely sports-effective component and determines the specific role of competition in the training. The classification of types of competitions. Characterized by specific features of the study (teaching), training and conditional qualifiers. Identified specific characteristics of qualifying and main events in the Special Olympics. It was determined that the competitions are important for the development of athletic skills, the creation of equal opportunities for competition. It was determined that the competitions are the best means of verifying the athlete athletic skills, measuring progress and providing incentives for personal growth.